2001
DOI: 10.4049/jimmunol.166.3.1912
|View full text |Cite
|
Sign up to set email alerts
|

The Hamster as a Model of Human Visceral Leishmaniasis: Progressive Disease and Impaired Generation of Nitric Oxide in the Face of a Prominent Th1-Like Cytokine Response

Abstract: Active human visceral leishmaniasis (VL) is characterized by a progressive increase in visceral parasite burden, cachexia, massive splenomegaly, and hypergammaglobulinemia. In contrast, mice infected with Leishmania donovani, the most commonly studied model of VL, do not develop overt, progressive disease. Furthermore, mice control Leishmania infection through the generation of NO, an effector mechanism that does not have a clear role in human macrophage antimicrobial function. Remarkably, infection of the Syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
259
4
11

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(290 citation statements)
references
References 48 publications
16
259
4
11
Order By: Relevance
“…Although some authors point out to the importance of IFN-γ in the resolution of leishmaniasis infection (Kaye et al 1991, Carvalho et al 1994, the IFN-γ expression levels detected at day 7, when Leishmania parasites were inoculated, apparently did not restrain the progression of L. infantum infection in co-infected mice. According to Melby et al (2001), syrian hamsters infected with L. donovani are not able to control parasite replication despite the high levels of Th 1 cytokine expression, namely IFN-γ, as observed in this study. In fact, co-infected mice presented an evident splenomegaly on day 56, which is a typical clinical symptom of visceral leishmaniasis, and positive cultures with high values of parasite density were observed.…”
Section: Discussionsupporting
confidence: 49%
“…Although some authors point out to the importance of IFN-γ in the resolution of leishmaniasis infection (Kaye et al 1991, Carvalho et al 1994, the IFN-γ expression levels detected at day 7, when Leishmania parasites were inoculated, apparently did not restrain the progression of L. infantum infection in co-infected mice. According to Melby et al (2001), syrian hamsters infected with L. donovani are not able to control parasite replication despite the high levels of Th 1 cytokine expression, namely IFN-γ, as observed in this study. In fact, co-infected mice presented an evident splenomegaly on day 56, which is a typical clinical symptom of visceral leishmaniasis, and positive cultures with high values of parasite density were observed.…”
Section: Discussionsupporting
confidence: 49%
“…Studies in the classical hamster model of VL also showed decreased expression of iNOS mRNA, accounting for defective parasite elimination, thereby enhancing disease progression (47). Indeed serum nitrite levels are also decreased in active VL (48), and our study corroborated that intracellular NO in macrophages of patients with VL (n 5 6) are significantly decreased as compared to healthy individuals (n 5 5), GMFC being 38.88 AE 25.44 vs. 212.70 AE 15.71 (P \ 0.05, Fig.…”
Section: Parasitized Macrophages Had Decreased Levels Of No That Was mentioning
confidence: 99%
“…This situation led to the experimental infection of the deer mouse Peromyscus maniculatus, a primary reservoir of the SNV 8 . However as in the golden hamster experimental model to study visceral leishmaniasis research is hindered by the lack of commercially available immunological and molecular reagents to investigate mechanisms of disease 25 .…”
Section: This Is the First Study That Examines P Yucatanicus Clinicamentioning
confidence: 99%